Solution of nonlinear equations via Padé approximation. A Computer Algebra approach - TRÎMBIȚAȘ , Radu T. (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
We generate automatically several high order numerical methods for the solution of nonlinear equations using Pad´e approximation and Maple CAS. Mathematics Subject Classification (2010): 65H05, 65D05, 65D99.